Big gardens in small spaces : out-of-the-box advice for boxed-in gardeners - Cox, Martyn (Timber Press, 2009)
Provides practical solutions for taking advantage of every square inch of a small space - including gardening in shady corners, on rooftops, around doorways, and in the cracks of pavement.